Comparing Data Treatments on Item‐Level Nonresponse and Their Effects on Data Analysis of Large‐Scale Assessments: 2009 PISA Study. Issue 1 (19th May 2015) - Chen, Haiwen H.; von Davier, Matthias; Yamamoto, Kentaro; Kong, Nan
Abstract : One major issue with large‐scale assessments is that the respondents might give no responses to many items, resulting in less accurate estimations of both assessed abilities and item parameters. This report studies how the types of items affect the item‐level nonresponse rates and how different methods of treating item‐level nonresponses have an effect on item calibration and scoring. Abstract : Report Number: ETS RR–15–12